2008
DOI: 10.1016/j.acn.2008.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological profile of Brazilian older adults with heterogeneous educational backgrounds

Abstract: Education significantly impacts cognitive performance of older adults even in the absence of dementia. Some cognitive tests seem less vulnerable to the influence of education and thus may be more suitable for cognitive assessment of older adults with heterogeneous backgrounds. The objective of this study was to investigate which tests in a cognitive battery were less influenced by educational levels in a sample of cognitively unimpaired older Brazilians. In addition, we evaluated the impact of very high educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
21

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 40 publications
2
32
1
21
Order By: Relevance
“…Controversially to our results, another study conducted in Brazil 8 showed that brief batteries could accurately discriminate MCI from normal and demented individuals, although not sensitively enough to establish subtypes of MCI (e.g., amnestic, non-amnestic or multiple domain). Our findings suggest that, at least in a sample that mirror clinical everyday clinical practice (i.e., clinical-control individuals, MCI and individuals with dementia), the use of this brief battery should be restricted to the purpose of determining less specific groups, such as: 1) individuals with no decline versus individuals with cognitive decline (normal versus MCI plus AD); or 2) individuals without AD (MCI plus normal individuals) from individuals with AD.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Controversially to our results, another study conducted in Brazil 8 showed that brief batteries could accurately discriminate MCI from normal and demented individuals, although not sensitively enough to establish subtypes of MCI (e.g., amnestic, non-amnestic or multiple domain). Our findings suggest that, at least in a sample that mirror clinical everyday clinical practice (i.e., clinical-control individuals, MCI and individuals with dementia), the use of this brief battery should be restricted to the purpose of determining less specific groups, such as: 1) individuals with no decline versus individuals with cognitive decline (normal versus MCI plus AD); or 2) individuals without AD (MCI plus normal individuals) from individuals with AD.…”
Section: Discussioncontrasting
confidence: 41%
“…Some studies in Brazil have proposed new neuropsychological batteries and brief screening tools for the diagnosis of both MCI and dementia [8][9][10][11] . Some studies have investigated single tests or existing batteries, such as the Clock Drawing Test (CDT) 12 , the Mini-Mental State Examination (MMSE) and the Cambridge Mental Disorders of the Elderly Examination (CAMDEX).…”
Section: Introductionmentioning
confidence: 99%
“…1,28 Evidence of objective memory impairment was defined as performance bellow 1.5 standard deviation in the memory tests (RBMT and/or FOME), adjusted for age and educational status. 29 Subjects without evidence of cognitive impairment were included in the control group.…”
Section: Diagnosismentioning
confidence: 99%
“…Diniz et al 22 evaluated elderly community residents and found statistically significant correlations between MMSE and age (rho = 0.232, p = 0.003) and education (rho = 0.471, p < 0.0001) and a significant correlation linked to sex, with men having better outcomes than women. Yassuda et al 48 studied the effect of formal education in a neuropsychological assessment battery comparing groups with different educational levels and reported that formal education is correlated with most of the instruments (MMSE, CAMCOG, Trail Making Test Part B, Vocabulary and Block Design, WAIS-R and Short Cognitive Performance Test) although no significant correlation with the Verbal Fluency Test was found. .…”
Section: Discussionmentioning
confidence: 99%
“…These findings will enhance future clinical studies on the protocol's applicability in the Brazilian population. Given its importance, the GC construct should be investigated further and additional measures included such as: socioeconomic status, income, educational level and occupational level 48 .…”
Section: Discussionmentioning
confidence: 99%